Farmers market food safety: A comprehensive review of training needs in the U.S. - Topalcengiz, Zeynal; Sirsat, Sujata A.; Acuff, Jennifer C.; Gibson, Kristen E. (Thomas A. Lyson Center for Civic Agriculture and Food Systems, 2024)
Farmers markets offer an apparently easy way for small-scale or hobbyist food producers to sell fresh produce, meat, and poultry from their farms or dis-tribute value-added products, but they may be unaware of the foodborne illness risks associated with both fresh produce and derivative products, as well as of their local food safety requirements. Food guidance and rules vary from state to state and market to market, making it difficult for indi-viduals to navigate the various regulatory levels. Even if a local food producer is exempt from these rules due to their amount of sales, they will still benefit greatly from resources and educational tools that increase awareness and knowledge of food safety best practices. This review discusses current knowledge of and guidelines for food safety in farmers markets based on peer-reviewed and grey literature as well as published guidelines and recommendations. We examine facilities and supplies, regulatory measures, education and train-ing, and Good Farmers Market Practices as preventive measures to enhance food safety in farmers markets, which are critical to local and regional food systems. Overall, we identified various barriers to implementing farmers market food safety standards and practices in this scoping review; removing these barriers will require the participation of local regularity authorities, market managers, vendors, and consumers. © 2024 by the Authors.
Keywords: cottage food; cross-contamination; education and training; facilities; farmers markets; food safety; fresh produce; Good Farmers’ Market Practices; local food system; manager; pathogen; regulations; value-added; vendor